2015
DOI: 10.1111/imm.12478
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4—leukotriene B4 receptor axis promotes oxazolone‐induced contact dermatitis by directing skin homing of neutrophils and CD8+ T cells

Abstract: SummaryLeukotriene B 4 (LTB 4 ) is a lipid mediator that is rapidly generated in inflammatory sites, and its functional receptor, BLT1, is mostly expressed on immune cells. Contact dermatitis is a common inflammatory skin disease characterized by skin oedema and abundant inflammatory infiltrates, primarily including neutrophils and CD8 + T cells. The role of the LTB 4 -BLT1 axis in contact dermatitis remains largely unknown. In this study, we found up-regulated gene expression of 5-lipoxygenase and leukotriene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…In order to demonstrate the location of LTA 4 H and BLT1 expression, skin and lung tissue sections from patients with SSc and healthy donors were subjected to double immunofluorescence staining for the myofibroblast marker α-SMA, endothelial cell marker CD31, macrophage marker CD68, T lymphocyte marker CD3, and resting fibroblast marker CD90. LTA 4 LTB 4 has been implicated as a chemoattractant for immune cells, especially neutrophils (12,13,23). However, in the present study, neutrophils were rarely seen in the lesional skin of SSc patients, being detected much less frequently than T lymphocytes or macrophages (see Supplementary Figure 1L [http://onlin elibr ary.wiley.com/doi/10.1002/art.41192/ abstract]).…”
Section: Local Up-regulation Of Ltb 4 Synthesis and Blt1mentioning
confidence: 49%
“…In order to demonstrate the location of LTA 4 H and BLT1 expression, skin and lung tissue sections from patients with SSc and healthy donors were subjected to double immunofluorescence staining for the myofibroblast marker α-SMA, endothelial cell marker CD31, macrophage marker CD68, T lymphocyte marker CD3, and resting fibroblast marker CD90. LTA 4 LTB 4 has been implicated as a chemoattractant for immune cells, especially neutrophils (12,13,23). However, in the present study, neutrophils were rarely seen in the lesional skin of SSc patients, being detected much less frequently than T lymphocytes or macrophages (see Supplementary Figure 1L [http://onlin elibr ary.wiley.com/doi/10.1002/art.41192/ abstract]).…”
Section: Local Up-regulation Of Ltb 4 Synthesis and Blt1mentioning
confidence: 49%
“…The ARA LOX product leukotriene B 4 (LTB 4 ) likewise promotes Th17 development (Chen et al, ). It also enhances B cell activation (Yamaoka et al, ) and is a chemoattractant for CD8 + T cells, neutrophils (Lv et al, ), and Th17 cells (Lee et al, ). Here, we observed that control diet‐fed females had lower levels of LTB 4 compared to control diet‐fed males.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the levels of LTB4 produced by BLM-stimulated macrophages are sufficient to promote TGF-b production by macrophages, which was not further enhanced by increasing the dose of exogenous LTB4, suggesting that LTB4 at low concentration is able to amplify TGF-b production by macrophages upon BLM stimulation, thereby leading to lung fibrosis. Thus, it is likely that LTB4 derived from macrophages could be sufficient to promote TGF-b production in an autocrine way, which further activates fibroblasts, whereas neutrophils, as a major source of LTB4, are important for providing LTB4 at higher levels to recruit more neutrophils and T cells to promote tissue inflammation (12,15,17,18). This may explain, at least in part, why depletion of neutrophils did not affect BLM-induced lung fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, BLT1-dependent neutrophil recruitment is important for the development of collageninduced arthritis and BLT1-dependent CD4 + T cell recruitment in allergic asthma (15,16). Our previous studies demonstrated that BLT1-mediated early recruitment of neutrophils, which act as a primary source of LTB4, is essential for skin infiltration of allergic-specific T cells, contributing to allergic skin inflammation (17,18). Accumulating evidence suggests that lung fibrosis is often linked to a strong inflammatory response, at least in the early phase (19).…”
mentioning
confidence: 99%